2014
DOI: 10.1371/journal.pone.0105934
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomised Controlled Effectiveness Trial Evaluating Perinatal Home Visiting among South African Mothers/Infants

Abstract: BackgroundInterventions are needed to reduce poor perinatal health. We trained community health workers (CHWs) as home visitors to address maternal/infant risks.MethodsIn a cluster randomised controlled trial in Cape Town townships, neighbourhoods were randomised within matched pairs to 1) the control, healthcare at clinics (n = 12 neighbourhoods; n = 594 women), or 2) a home visiting intervention by CBW trained in cognitive-behavioural strategies to address health risks (by the Philani Maternal, Child Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 30 publications
1
91
3
Order By: Relevance
“…21,39 Home visits by trained nurses or community health workers can be introduced to circumvent challenges such as expensive transport, long waiting lines, and discordant mother-infant clinic appointments, 36 and by extension enhance maternal and child outcomes. 39,41 Our finding that stigma and other psychosocial factors did not increase the odds of MTCT differs from prior studies in the region that have found that fears of HIV-related stigma and discrimination negatively impact service uptake and adherence at each step of the PMTCT cascade.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…21,39 Home visits by trained nurses or community health workers can be introduced to circumvent challenges such as expensive transport, long waiting lines, and discordant mother-infant clinic appointments, 36 and by extension enhance maternal and child outcomes. 39,41 Our finding that stigma and other psychosocial factors did not increase the odds of MTCT differs from prior studies in the region that have found that fears of HIV-related stigma and discrimination negatively impact service uptake and adherence at each step of the PMTCT cascade.…”
Section: Discussioncontrasting
confidence: 90%
“…39,40 In addition, health systems should aim not only to provide knowledge to women but also to cultivate a supportive relationship that enables the women to apply the new knowledge to their daily lives, and come up with solutions to challenges to healthy daily routines. 36,41 This can only happen if patient-provider communication is improved at every stage of the continuum of care. 42 For example, it may include being an encourager during the testing stage, providing knowledge and reassurance during the early stages of care, and becoming a partner in health as care becomes more established.…”
Section: Discussionmentioning
confidence: 99%
“…Our research suggests that not only should the intensity of efforts to reduce MM not slacken, the findings also add to calls to move beyond vertical interventions aimed at proximate causes of MM, in order to provide strengthening for health systems that links maternal, newborn and child health (Jimenez Soto et al, 2012;Odeny et al, 2014;Rotheram-Borus et al, 2014;Spector et al, 2012), as well as for social protection systems, which affirmatively ameliorate gendered burdens of unpaid care work and include incentives for fathers to take part in caring for their children. Further, both public and targeted education campaigns (e.g.…”
Section: Conclusion and Recommendationsmentioning
confidence: 77%
“…For example, while strong evidence of effectiveness has been demonstrated for the Triple P Program [142][143][144][145][146] the Positive Action Program; 147,148) and the NurseFamily Partnership Programs, 150) there is a need for more evidence concerning the effectiveness of social support and the media format programs for reducing child maltreatment. Also, in many evaluation studies, risk factors for child abuse (e.g., changes in parents' attitudes towards discipline) are used to evaluate effectiveness rather than the direct measure of reports of child abuse.…”
Section: )mentioning
confidence: 99%
“…Home visitation programs have been shown in the US to prevent child maltreatment. 149) A home visiting program in South Africa 150) suggests that more visits are associ-ated with increased cognitive development in the infants enrolled. In the US, the Domestic Violence Enhanced Home Visitation Program (DOVE) which combines 2 evidencebased interventions, a 10-minute brochure-based IPV intervention to be used within home visitation, has been tested in an a randomized controlled trial and demonstrated decreased IPV.…”
Section: Enhancing Resilience By Understanding the Impact Of Traumamentioning
confidence: 99%